Genome-Wide SNPs Clarify a Complex Radiation and Support Recognition of an Additional Cat Species. (28th July 2021) - Trindade, Fernanda J; Rodrigues, Maíra R; Figueiró, Henrique V; Li, Gang; Murphy, William J; Eizirik, Eduardo
Abstract: Phylogenetic reconstruction and species delimitation are often challenging in the case of recent evolutionary radiations, especially when postspeciation gene flow is present. Leopardus is a Neotropical cat genus that has a long history of recalcitrant taxonomic problems, along with both ancient and current episodes of interspecies admixture. Here, we employ genome-wide SNP data from all presently recognized Leopardus species, including several individuals from the tigrina complex (representing Leopardus guttulus and two distinct populations of Leopardus tigrinus ), to investigate the evolutionary history of this genus. Our results reveal that the tigrina complex is paraphyletic, containing at least three distinct species. While one can be assigned to L. guttulus, the other two remain uncertain regarding their taxonomic assignment. Our findings indicate that the "tigrina" morphology may be plesiomorphic within this group, which has led to a longstanding taxonomic trend of lumping these poorly known felids into a single species.